2000
DOI: 10.1111/j.1600-0587.2000.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Succession of boreal forest spider assemblages following wildfire and harvesting

Abstract: To test whether spider succession following harvest differed from succession following wildfire, spiders were collected by pitfall trapping and sweep netting over two years in aspen‐dominated boreal forests. Over 8400 individuals from 127 species of spiders were identified from 12 stands representing three age‐classes (stand origin in 1995, 1982, and 1968) and two disturbance types (wildfire and harvesting). The diversity of spider assemblages tended to be higher in fire‐origin stands than in harvest‐origin st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 35 publications
5
91
3
2
Order By: Relevance
“…Informed management of chestnut forests requires an understanding of ecosystem resilience. While Baker et al (2004) found little difference between the beetle fauna after logging or wildfire treatments in Tasmanian forests, Buddle et al (2000) and Saint-Germain et al (2005) observed a significant divergence in spiders' and carabid beetles' responses to such disturbancesin boreal forests. Could patch-wise clearfelling and harvesting be a way of preserving a fire-adapted biodiversity without the negative effects of forest fires (emissions and erosion), and at the same time allow for the production of valuable chestnut timber?…”
Section: Implications For Forest Managementmentioning
confidence: 93%
“…Informed management of chestnut forests requires an understanding of ecosystem resilience. While Baker et al (2004) found little difference between the beetle fauna after logging or wildfire treatments in Tasmanian forests, Buddle et al (2000) and Saint-Germain et al (2005) observed a significant divergence in spiders' and carabid beetles' responses to such disturbancesin boreal forests. Could patch-wise clearfelling and harvesting be a way of preserving a fire-adapted biodiversity without the negative effects of forest fires (emissions and erosion), and at the same time allow for the production of valuable chestnut timber?…”
Section: Implications For Forest Managementmentioning
confidence: 93%
“…Ciertos estudios han mostrado que la estructura de la comunidad de arañas se ve afectada por las perturbaciones antrópicas (Buddle et al 2000, Podgaiski et al 2013) y el manejo de la tierra (Downie et al 1999, Noel y Finch 2010, por ello los estudios ecológicos de las arañas como indicadoras de calidad ambiental se han incrementado en la actualidad (Scott et al 2006, Castiglioni et al 2017.…”
Section: Introductionunclassified
“…Consequently, it is important to advice that management planning should avoid maintaining traditional coppice stand (i.e., regular clear-cutting every 15 years, which would produce young phases). Such effects, associated with the removal of trees and the clear-cut harvesting have not been directly investigated here but due to the colonization of open-habitat species ,we may expect an increase of diversity, mainly due to the appearance of open-habitat species (Buddle et al 2000;Pearce and Venier 2006). In this case, species richness as such may not represent a valid criterion for successful conservation or forest management, but the focus should be on species that suffer from forestry operations as these are currently under severe threat.…”
Section: Managementmentioning
confidence: 99%
“…Most of the studies concerning the influence of forest management on arthropod assemblages focused on the effects of clear-cutting (Paradis and Work 2011), fire (Buddle et al 2000 and references herein), successional phase of the forest (Christensen and Emborg 1996;Grgič and Kos 2005), and forest fragmentation (Pajunen et al 1995). Pearce and Venier (2006) reviewed the use of spiders and ground beetles as bioindicators in different forest managements, highlighting that both in ground beetles and spiders, clear-cutting induces changes in the composition of the community, such as shifts in the assemblage dominance from forest to open-habitat species (Buddle et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation